Does open innovation enhance a large firm's financial sustainability? A case of the Korean food industry - Harry Jeong; Kwangsoo Shin; Eungdo Kim; Seunghyun Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study aims to explore whether a firm's financial sustainability is enhanced by open innovation especially after a global financial crisis. There are few studies on the relationship between open innovation and financial sustainability. This study aimed to fill the literature gap by analyzing the change in the financial ratio according to the increase or decrease in open innovation. We used a case study method regarding large Korean food firms. Korea is a latecomer in the food industry, which is driven by large companies. This study is meaningful for financial sustainability studies of countries with a lack of resources and small market size, which require open innovation. The findings of this study are as follows: The most preferred alliance strategy of large food firms is joint research. In order to secure raw materials and markets, open innovation was actively conducted abroad, which increased growth and profitability. However, a firm which rarely adopts open innovation could grow steadily through internal strategies. On the other hand, although relatively many open innovations have been used, growth and profitability could decrease. Firms with sufficient absorptive capacity strengthen financial sustainability through open innovation.
Keywords: 650; food industry; financial sustainability; open innovation; value chain; financial stability